Embolization of an Unruptured Distal Lenticulostriate Aneurysm Associated with Moyamoya Disease - Harreld, J.H.; Zomorodi, A.R. (American Journal of Neuroradiology, 2011)
SUMMARY: Lenticulostriate aneurysms are rare and usually present with intracranial hemorrhage, limiting understanding of their natural course. We describe an unusual case of an unruptured rapidly growing distal LSA aneurysm in the setting of Moyamoya disease, successfully embolized with n-BCA following functional neurologic testing with amobarbital. n-BCAn-butyl cyanoacrylateMCAmiddle cerebral arteryACAanterior cerebral arteryLSAlenticulostriate arteryDSAdigital subtraction angiography